Adding... it's easy, isn't it?

Algebra Level 4

Let f ( x , y ) = 2 x + 3 y 2 x + 2 y f(x,y)\quad =\quad \frac { 2x+3y }{ { 2 }^{ x+2y } }

For intergers x 0 y 0 x\ge 0\\ y\ge 0 ,

find the sum of all f ( x , y ) f(x,y)


The answer is 8.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Tan Wee Kean
Aug 31, 2014

For y y constant, the sum of all f ( x , y ) f(x,y) is x = 0 ( 2 x + 3 y 2 x + 2 y ) = 2 x = 0 ( 2 x + 3 y 2 x + 2 y ) x = 0 ( 2 x + 3 y 2 x + 2 y ) = x = 0 ( 2 x + 3 y 2 x + 2 y 1 ) x = 0 ( 2 x + 3 y 2 x + 2 y ) = 3 y 2 2 y 1 + x = 1 ( 2 x + 3 y 2 x + 2 y 1 ) x = 0 ( 2 x + 3 y 2 x + 2 y ) = 3 y 2 2 y 1 + x = 0 2 2 x + 2 y = 3 y 2 2 y 1 + x = 0 1 2 x + 2 y 1 = 3 y 2 2 y 1 + x = 0 2 1 2 y x \sum _{ x=0 }^{ \infty }{ ( } \frac { 2x+3y }{ { 2 }^{ x+2y } } )=\quad 2\sum _{ x=0 }^{ \infty }{ ( } \frac { 2x+3y }{ { 2 }^{ x+2y } } )-\sum _{ x=0 }^{ \infty }{ ( } \frac { 2x+3y }{ { 2 }^{ x+2y } } )=\sum _{ x=0 }^{ \infty }{ ( } \frac { 2x+3y }{ { 2 }^{ x+2y-1 } } )-\sum _{ x=0 }^{ \infty }{ ( } \frac { 2x+3y }{ { 2 }^{ x+2y } } )=\frac { 3y }{ { 2 }^{ 2y-1 } } +\sum _{ x=1 }^{ \infty }{ ( } \frac { 2x+3y }{ { 2 }^{ x+2y-1 } } )-\sum _{ x=0 }^{ \infty }{ ( } \frac { 2x+3y }{ { 2 }^{ x+2y } } )=\frac { 3y }{ { 2 }^{ 2y-1 } } +\sum _{ x=0 }^{ \infty }{ \frac { 2 }{ { 2 }^{ x+2y } } } =\frac { 3y }{ { 2 }^{ 2y-1 } } +\sum _{ x=0 }^{ \infty }{ \frac { 1 }{ { 2 }^{ x+2y-1 } } } =\frac { 3y }{ { 2 }^{ 2y-1 } } +\sum _{ x=0 }^{ \infty }{ { 2 }^{ 1-2y-x } } .

Then, note that n = k 2 z n = 2 z + 1 k \sum _{ n=k }^{ \infty }{ { 2 }^{ z-n } } ={ 2 }^{ z+1-k } .

In this case, z = 1 2 y , k = 0 z=1-2y,\quad k=0 so simplifying 3 y 2 2 y 1 + x = 0 2 1 2 y x = 3 y 2 2 y 1 + 2 2 2 y \frac { 3y }{ { 2 }^{ 2y-1 } } +\sum _{ x=0 }^{ \infty }{ { 2 }^{ 1-2y-x } } =\frac { 3y }{ { 2 }^{ 2y-1 } } +{ 2 }^{ 2-2y } which is the sum of f ( x , y ) f(x,y) for y constant and x 0 x\ge 0

Then the sum of all f ( x , y ) f(x,y) for both y , x 0 y,x\ge 0 is y = 0 ( 3 y 2 2 y 1 + 2 2 2 y ) \sum _{ y=0 }^{ \infty }{ (\frac { 3y }{ { 2 }^{ 2y-1 } } +{ 2 }^{ 2-2y } } )

Let S 1 = y = 0 3 y 2 2 y 1 = 0 + 3 2 + 6 8 + 9 32 + 12 64 + . . . { S }_{ 1 }=\sum _{ y=0 }^{ \infty }{ \frac { 3y }{ { 2 }^{ 2y-1 } } } =0+\frac { 3 }{ 2 } +\frac { 6 }{ 8 } +\frac { 9 }{ 32 } +\frac { 12 }{ 64 } +...

S 2 = y = 0 2 2 2 y = 4 + 1 + 1 4 + 1 16 + 1 64 + . . . { S }_{ 2 }=\sum _{ y=0 }^{ \infty }{ { 2 }^{ 2-2y } } =4+1+\frac { 1 }{ 4 } +\frac { 1 }{ 16 } +\frac { 1 }{ 64 } +...

Then,

4 S 1 = 0 + 6 + 6 2 + 9 8 + 12 32 + . . . 4 S 1 S 1 = 3 S 1 = 6 + 3 2 + 3 8 + 3 32 + . . . S 1 = 2 + 1 2 + 1 8 + 1 32 + . . . 4 S 1 = 8 + 2 + 1 8 + . . . 4 S 1 S 1 = 3 S 1 = 8 S 1 = 8 3 4{ S }_{ 1 }=0+6+\frac { 6 }{ 2 } +\frac { 9 }{ 8 } +\frac { 12 }{ 32 } +...\\ 4{ S }_{ 1 }-{ S }_{ 1 }=3{ S }_{ 1 }=6+\frac { 3 }{ 2 } +\frac { 3 }{ 8 } +\frac { 3 }{ 32 } +...\\ { S }_{ 1 }=2+\frac { 1 }{ 2 } +\frac { 1 }{ 8 } +\frac { 1 }{ 32 } +...\\ 4{ S }_{ 1 }=8+2+\frac { 1 }{ 8 } +...\\ 4{ S }_{ 1 }-{ S }_{ 1 }=3{ S }_{ 1 }=8\\ { S }_{ 1 }=\frac { 8 }{ 3 }

Similarly,

4 S 2 = 16 + 4 + 1 + 1 4 + 1 16 + . . . 4 S 2 S 2 = 3 S 2 = 16 S 2 = 16 3 4{ S }_{ 2 }=16+4+1+\frac { 1 }{ 4 } +\frac { 1 }{ 16 } +...\\ 4{ S }_{ 2 }-{ S }_{ 2 }=3{ S }_{ 2 }=16\\ { S }_{ 2 }=\frac { 16 }{ 3 }

Finally, S 1 + S 2 = 24 3 = 8 { S }_{ 1 }+{ S }_{ 2 }=\frac { 24 }{ 3 } =\boxed{8}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...